Legal Analysis of The Role of Notaries in The Drafting of Financing Agreement Deeds Based on Sharia Principles At PT. Bank Syariah Indonesia Batam Branch Office - Bayang Maneshakerti; Laily Washliati; Muhammad Tartib; Soerya Respationo; Erniyanti Erniyanti (FKIP, Universitas Palangka Raya, 2024)
In every transaction or agreement they observe, notaries are crucial in guaranteeing adherence to sharia rules. It is essential for notaries to comprehend sharia principles in muamalah (business transactions) in order to perform their duties responsibly and in compliance with applicable legal rules. Muamalah based on sharia principles addresses a number of topics, including justice, openness, unity, and adherence to Islamic legal norms. To determine if a transaction or agreement complies with the relevant sharia principles, notaries must comprehend and internalise these principles. This research aims to find out, analyse and explain in depth the role of notaries in making financing agreement deeds based on sharia principles, so that they can contribute to the development of Islamic banking law and notaries in Indonesia, and analyse and explain comprehensively the responsibilities of notaries both civilly, criminally, and administratively for the sharia financing agreement deeds they make, so that they can contribute to the legal protection of the par. This research uses a type of legal research that is Normative as well as Sociological (empirical). The findings revealed that the role of the Notary in the application of Sharia principles in contract deeds at Bank Syariah Indonesia KC Batam is not overly dominant, because the Notary's role is essentially limited to legalising the contract, while the bank determines the contract's content entirely. The notary bears accountability for the Sharia Financing Agreement deed and must read and comprehend its contents. With this reading, the notary can also amend any inaccuracies in the deed's contents. The Notary will refuse to legalise the deed if it violates the law, public order, or decency. The constraints of the absence of Notary competencies that are in accordance with and fulfill sharia provisions, make not all Notaries who are partners of Islamic banks lack understanding of sharia principles.